On some tridiagonal k-Toeplitz matrices: Algebraic and analytical aspects. Applications - Álvarez-Nodarse, R. (2005)
In this paper, we use the analytic theory for 2 and 3-Toeplitz matrices to obtain the explicit expressions for the eigenvalues, eigenvectors and the spectral measure associated to the corresponding infinite matrices. As an application we consider two solvable models related with the so-called chain model. Some numerical experiments are also included.